(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
This article is about mathematical modeling of the dependence of the moisture properties of different textile fabrics on geometric properties. The article builds a mathematical model of various towel products using the spss statistics program to determine the moisture properties of the hair thread and the geometric parameters of its shape in the fabric.